ENVIRONMENT OF APPLICATION: PRIMARY SCHOOLS AND SCHOOLS OF SOCCER (Fiep Bulletin - online, 2015)
We live, at the present time, a paradoxical situation in what refers to the sport. On one hand, from the social point of view, the sport probably constitutes an universal cultural phenomenon that defines it, as the most important human physical activity  Today's soccer is characterized to be carried out to an intense rhythm that requires of the players the maximum zeal. For this it becomes necessary to refer to the teaching form at level of infantile soccer.  In a first one he/she leaves it develops the concept of the different preparation from the sport initiation to level of training they are: 1) the Physical Preparation.  2) the Technical Preparation.  3) the Mental Preparation. 4) the Tactical Preparation. And the stages of development of sport formation. And the factors that determine it and their relationship with the orientation to the soccer at infantile level, in the Argentinean.  Also intent through I articulate, to diffuse and to inform on which is my position and to point out the because of my foundations with regard to the topic of the infantile sport in General and infantile Soccer in particular, according to my experience there for the year 1979, from now on and to have formed, some of the first schools of infantile Soccer that appeared in the city of Buenos Aires, Argentina.In second it leaves it exposes the concept in the different ways of works. In both sections, practical examples are presented for their improvement.     We consider that the sport, is a means of education and not an end in itself, therefore, we cannot ignore all the contributions of the Sciences from the Physical Education to the teaching of the sport. We also recognize that the sport training offers us an important help as for that it is through its channels that we should face the process of Sport Learning.
Keywords: .